The Implemention Of Cooperative Script Learning Model Toward Students’ Achievement In Ipa Lesson On Healthy Environment Materials And Environment Unhealthy At Third Grade Students’ In Sdn 05 Perawang In Academic Year 2016/2017 - Mariati Mariati (Jurnal Ilmiah Pendidikan Scholastic, 2018)
Based on observations made through interviews and direct observation in SD Negeri 05 Tualang, in the learning process there are obstcles, including student learning outcomes are still low. The condition is clearly visible from the average value of the daily tests conducted earlier IPA as many as 100 students (66.66%) of the 3 classes that reach KKM 75. Based on the problem above, the problem in this research is "How does Application of Cooperative Learning Model Assisted script Against Student Worksheet Improved Learning Outcomes At Subject IPA On Healthy Environment Materials and Environment Unhealthy at the third grade students in SDN 05 Perawang in academic Year 2016/2017 ". This research has been done for 3 months, namely the month of February 2017 until April 2017. The research was conducted in the third class of SDN 05 Perawang, kecamatan Tualang kabupaten Siak. There are two Sources of data of this classroom action derived from the subject of primary research and from not a secondary subject. Technique of collecting data of this research in the form of test. While the data collection tools include documentation, tests and observations. Documents used to obtain data about the ability to conduct learning activities using LKS before the research that is in the form of a list of values ​​/ reports assessment, processing and analysis. The test is used to obtain data about students' ability to work on LKS problems. Observation is using the assessment sheet that is to know the student activity and cohesiveness of the group in doing activities working on LKS. There is a learning outcome model-assisted learning Cooperative Script LKS toward improving student learning outcomes in science subjects to Content Healthy Environment and Environmental Unhealthy third class of SDN 05 Perawang in academic year2016/2017.Improved learning outcomes can be seen from the mean value in every cycle.In the initial cycle of the lowest score at number 50 there are 10 students, on the 1st cycle the lowest score 65 there are 8 students and in the final cycle the lowest score of 70 there are 2 students.While for the highest score in the initial cycle is the value of 100 with 1 student, the highest score of I is 85 as many as 85 students and the final cycle of the highest score is 100 as many as 4 students.So the use of Application of Learning Model Cooperative Script Against Assisted LKS Improved Learning Outcomes At Subject Matter Healthy Environment Science and Environment Unhealthy third class of SDN 05 Perawang in academic year.2016/2017.